Deconstructing Merge and Move to Make Room for Adjunction. (September 2015) - Hunter, Tim
Abstract This paper explores the syntactic and semantic properties of movement and adjunction and proposes a new analysis of these two phenomena according to which they are closely related to each other. The basic pieces of grammatical machinery that carry out movement also carry out adjunction. Building on independently appealing ideas concerning neo‐Davidsonian semantic composition and "move as re‐merge, " the proposed framework naturally accounts for (i) adjuncts' puzzling status "either inside or outside" a maximal projection, (ii) adjuncts' ability to escape reconstruction, and (iii) the prohibition on extraction from adjuncts.